A combined experimental-computational investigation on water adsorption in various ZIFs with the SOD and RHO topologies. Issue 69 (27th November 2018) - Gao, Meizhen; Wang, Jing; Rong, Zhenghao; Shi, Qi; Dong, Jinxiang
Abstract : Our results demonstrated that the contribution of vdW interactions is negligible and the contribution of electrostatic interactions plays a dominant role in the water adsorption in ZIFs. Abstract : We synthesized a series of seven zeolitic imidazolate frameworks (ZIFs), namely ZIF-8, ZIF-90, SIM-1, MAF-6, ZIF-25, ZIF-93 and ZIF-97. Then we investigated the adsorption behavior of water for each ZIF via a combined experimental-computational method. We focused on the van der Waals (vdW) and electrostatic contributions to their water adsorption capacity. The results showed that the vdW interactions were negligible and that electrostatic interactions played a dominant role. Moreover, we studied the effects of topology in the [Zn(almeIm)2 ] system with the same linker, 4-methylimidazole-5-carbaldehyde (almeIm). We found that SIM-1 with a smaller pore size and higher density exhibited greater water adsorption at low relative pressures, and in contrast, ZIF-93 with a larger pore size and lower density had significantly higher adsorption capacity at high relative pressures.